2010
DOI: 10.1007/978-3-642-14139-3_45
|View full text |Cite
|
Sign up to set email alerts
|

Parameter-Free Symmetry-Preserving Regularization Modelling of Turbulent Natural Convection Flows

Abstract: Since direct numerical simulations of natural convection flows cannot be performed at high Ra-numbers, a dynamically less complex mathematical formulation is sought. In the quest for such a formulation, we consider regularizations (smooth approximations) of the nonlinearity. The regularization method basically alters the convective terms to reduce the production of small scales of motion by means of vortex stretching. In doing so, we propose to preserve the symmetry and conservation properties of the convectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…The work in F.X. Trias thesis [52] and the aforementioned thesis, showed that kinetic energy preserving discretisations are critical for the accurate simulation of turbulent flows in the incompressible regime. Hence, they are also applied throughout this thesis and shown to yield accurate results.…”
Section: Background At the Cttcmentioning
confidence: 99%
“…The work in F.X. Trias thesis [52] and the aforementioned thesis, showed that kinetic energy preserving discretisations are critical for the accurate simulation of turbulent flows in the incompressible regime. Hence, they are also applied throughout this thesis and shown to yield accurate results.…”
Section: Background At the Cttcmentioning
confidence: 99%